2020
DOI: 10.1371/journal.pmed.1003151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physicians’ participation in non-interventional post-marketing studies on their prescription habits: A retrospective 2-armed cohort study in Germany

Abstract: Background Non-interventional post-marketing studies (NIPMSs) sponsored by pharmaceutical companies are controversial because, while they are theoretically useful instruments for pharmacovigilance, some authors have hypothesized that they are merely marketing instruments used to influence physicians' prescription behavior. So far, it has not been shown, to our knowledge, whether NIPMSs actually do have an influence on prescription behavior. The objective of this study was therefore to investigate whether physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…This rate is comparable to that observed for postmarket clinical studies overall, which are primarily sponsored by industry, 32 frequently evaluate new therapeutic uses, 33,34 and may play a role in promoting medication use after approval. 35 This has also been observed for therapeutics receiving accelerated approval designation, which are integrated into clinical practice, including new applications, without confirmation of clinical benefit for original indications. 36 New prospective clinical studies investigating therapeutic uses not included in their original approved indications may reflect interest in generating evidence for anticipated off-label uses.…”
Section: Discussionmentioning
confidence: 95%
“…This rate is comparable to that observed for postmarket clinical studies overall, which are primarily sponsored by industry, 32 frequently evaluate new therapeutic uses, 33,34 and may play a role in promoting medication use after approval. 35 This has also been observed for therapeutics receiving accelerated approval designation, which are integrated into clinical practice, including new applications, without confirmation of clinical benefit for original indications. 36 New prospective clinical studies investigating therapeutic uses not included in their original approved indications may reflect interest in generating evidence for anticipated off-label uses.…”
Section: Discussionmentioning
confidence: 95%
“…This trial was conducted between March 2006 and February 2007, and had an identical design and outcome, and planned the same ratio patient/investigator, but included fewer participants and was still unpublished. Non-interventional postmarketing studies seem suspicious especially since it has been shown that participating physicians prescribe more of the investigated drug 17. It is worth noting that the PAXIL (paroxetine) study 329 is a well-described example of mismatches between marketing claims made in the study and the data shown in an independent reanalysis 18.…”
Section: Discussionmentioning
confidence: 99%
“…Non-interventional postmarketing studies seem suspicious especially since it has been shown that participating physicians prescribe more of the investigated drug. 17 It is worth noting that the PAXIL (paroxetine) study 329 is a well-described example of mismatches between marketing claims made in the study and the data shown in an independent reanalysis. 18 There were also Open access major documented breaches in scientific integrity for paroxetine, including a ghost management programme ironically called CASSPER (Case Study for Peer Review).…”
Section: Statement Of Principal Findingsmentioning
confidence: 97%
“…Previous studies have noted that postmarket clinical studies by industry sponsors frequently evaluate new therapeutic uses, 14 while others have suggested they play a role in promoting medication use after approval. 30 This has been observed for therapeutics receiving accelerated approval designation, which are integrated into clinical practice, including new applications, without confirmation of clinical benefit for original indications. 31 We also identified PMRs and PMCs describing new prospective clinical studies potentially investigating modified or new indications.…”
Section: Discussionmentioning
confidence: 99%